2017
DOI: 10.1016/j.bandl.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Mens inversus in corpore inverso? Language lateralization in a boy with situs inversus totalis

Abstract: Situs inversus totalis is a rare condition where the visceral organs are organized as a mirror image of default organ position. In this study we picture the co-development between brain and visceral organs in a case of situs inversus totalis from a fetal stage to adolescence and compare our findings to an age-, gender-, and education-matched control with normal position of thoracic and abdominal organs. We show that in this case of situs inversus, functional and structural brain lateralization do not coincide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…In contrast with the first report, the second study suggests an increased probability of atypical language dominance in SIT and a possible link with reversal of the cerebral torque, but here two participants showed weak left/right handedness and the other suffered from left temporal lobe epilepsy (Ihara et al 2010). A recent case-study, described typical left-lateralized neural language organization in a right handed boy with SIT that showed reversed frontal and occipital petalia (Schuler et al 2017).…”
Section: Take Down Policycontrasting
confidence: 87%
“…In contrast with the first report, the second study suggests an increased probability of atypical language dominance in SIT and a possible link with reversal of the cerebral torque, but here two participants showed weak left/right handedness and the other suffered from left temporal lobe epilepsy (Ihara et al 2010). A recent case-study, described typical left-lateralized neural language organization in a right handed boy with SIT that showed reversed frontal and occipital petalia (Schuler et al 2017).…”
Section: Take Down Policycontrasting
confidence: 87%
“…Some studies based on small samples have suggested that aspects of brain structural asymmetry can be altered in SI [74][75][76][77] . Indeed, this was previously assessed in the same SI subjects and controls as analyzed in the present study 29,78 -briefly, planum temporale and arcuate fasciculus asymmetries were not altered in SI, but the overall cerebral torque showed evidence of left-right reversal in non-PCD SI.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal symmetry of the brain -both increased asymmetry as well as decreased asymmetry -has been reported in dyslexics (5,13,39). Whereas some studies report a typical left hemispheric language lateralization in the SI brain, others report a reversal of the language center to the opposite hemisphere (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…While DD has been associated with various anatomical and functional changes in the brain (21), a handful of reports have investigated brain anatomy and functionality in individuals with situs inversus (for example (22)(23)(24)(25)(26)). Interestingly, a range of neurodevelopmental disorders, such as autism, schizophrenia and DD, has been associated with laterality defects in the brain (27).…”
Section: Introductionmentioning
confidence: 99%